(untitled) (LACCEI, 2024)
Communicative competence is key to the professional development of various specialties, both in sciences and humanities. Thus, the present case study aimed to understand what communicative and methodological factors are used by two professors from two different faculties, one with a humanistic approach such as Psychology and with a focus on sciences such as Engineering from a private University in the city of Lima, Peru. Doing so, we seek to understand in depth the dimensions that make up this competence and methodological practice in order to identify the behaviors and actions that compose them. The research began with the theoretical review of the basic concepts of communicative and methodological teaching competence, depending on the use of space, resources, techniques, dynamics, exercises and language management within the classroom. Then two diagnostic instruments were systematized and proposed based on them. Then we proceeded to the validation and improvement of these instruments, the methodological design, the selection of the study subjects, the observation of the sessions and finally the analysis of the results and the corresponding conclusions of the same. The study showed that the four dimensions defined in the study of this case correspond to demonstrable behaviors within the teaching practices of the study subjects. However, the research managed to show that not all dimensions are executed consciously by teachers.